2007
DOI: 10.1007/s00213-006-0650-6
|View full text |Cite
|
Sign up to set email alerts
|

The disruptive effects of the CB1 receptor antagonist rimonabant on extinction learning in mice are task-specific

Abstract: Rationale-Disruption of CB 1 receptor signaling through the use of CB 1 (-/-) mice or the CB 1 receptor antagonist rimonabant (SR141716) has been demonstrated to impair extinction of learned responses in conditioned fear and Morris water maze tasks. In contrast, CB 1 (-/-) mice exhibited normal extinction rates in an appetitively motivated operant conditioning task.Objectives-The purpose of this study was to test whether rimonabant would differentially disrupt extinction learning between fear-motivated and foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
71
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 39 publications
(51 reference statements)
12
71
3
Order By: Relevance
“…Indeed, the importance of CB 1 receptors in the extinction of aversive memories has been substantiated by several groups in different behavioral paradigms using systemic administration. CB 1 receptor antagonists were found to impair extinction in fear-related (Marsicano et al, 2002;Suzuki et al, 2004;Chhatwal et al, 2005;Reich et al, 2008) and non-fear-related paradigms (Varvel and Lichtman, 2002), with no effect on appetitively motivated learning tasks (Hölter et al, 2005;Niyuhire et al, 2007;Harloe et al, 2008). Reich et al (2008) found that administrating AM251 enhances acquisition of freezing behavior and impairs extinction in trace and delay pavlovian fear conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the importance of CB 1 receptors in the extinction of aversive memories has been substantiated by several groups in different behavioral paradigms using systemic administration. CB 1 receptor antagonists were found to impair extinction in fear-related (Marsicano et al, 2002;Suzuki et al, 2004;Chhatwal et al, 2005;Reich et al, 2008) and non-fear-related paradigms (Varvel and Lichtman, 2002), with no effect on appetitively motivated learning tasks (Hölter et al, 2005;Niyuhire et al, 2007;Harloe et al, 2008). Reich et al (2008) found that administrating AM251 enhances acquisition of freezing behavior and impairs extinction in trace and delay pavlovian fear conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the endocannabinoid system in fear responding per se (i.e. in the absence of nociceptive tone) has been examined extensively and the weight of evidence suggests that endocannabinoid-CB 1 receptor signalling serves to facilitate and enhance the extinction of conditioned fear responding (for review see [15,48,79]), while genetic deletion or pharmacological blockade of the CB 1 receptor attenuates short-and long-term extinction of conditioned fear responding [14,18,25,39,44,48,52,59,62,70,76]. The results of the present study, however, suggest that in the presence of formalin-evoked nociceptive tone, increased endocannabinoid signalling in the vHip (as a consequence of URB597 administration) in fact serves to inhibit rather than enhance the short-term, within-trial extinction of fear responding.…”
Section: Discussionmentioning
confidence: 99%
“…CB1-deficient mice show impaired auditory fear extinction, with unaffected memory acquisition and consolidation (Marsicano et al 2002), whereas systemic and local cannabinoid receptor activation facilitate fear extinction (Chhatwal et al 2005;Pamplona et al , 2008Abush and Akirav 2010). So far, however, these findings on the involvement of CB1 receptors in extinction processes seem limited to aversive learning tasks, indicated by studies showing that CB1 receptors are not required in appetitive tasks (Hölter et al 2005;Niyuhire et al 2007). …”
mentioning
confidence: 99%